An Investigation on the Influence of Various Biochemical Tenderness Factors on Eight Different Bovine Muscles - P. A. Hammond; C. K. Chun; W. Wu; A. A. Welter; T. G. O'Quinn; G. Magnin-Bissel; E. Geisbrecht; M. D. Chao (Kansas Agricultural Experiment Station Research Reports, 2022)
Objective:Beef tenderness is a complex palatability trait with many tenderness-contributing components. The objective of this study is to understand the relative contribution of each tenderness component to eight different beef muscles. Study Description:Top sirloin butt, ribeye, brisket, flank, knuckle, eye of round, mock tender, and shoulder clod were collected from 10 U.S. Department of Agriculture high choice beef carcasses and assigned to a 2- or 21-day aging period (n = 160). Protein degradation, collagen content, mature collagen crosslink density, intramuscular lipid content, pH, shear force, and trained sensory panel analysis were determined. A Pearson correlation analysis was used to determine the relationship between each tenderness contributor measured in this study to the overall tenderness evaluated by the trained panelist. Results:Overall tenderness of ribeye, flank, eye of round, and shoulder clod were largely driven by the protein degradation of muscle fibers (effect of aging). On the other hand, overall tenderness for brisket was determined by collagen content and crosslink density (effect from connective tissue). Finally, overall tenderness of top sirloin butt was strongly correlated with lipid content. When all the cuts were combined together and analyzed as a whole (n = 160), all of the biochemical measurements conducted in this study played a small but important role as an overall tenderness contributor. The Bottom Line:Results from this study filled in some of the knowledge gap on the relative contribution of each tenderness component to the overall perception of tenderness from each cut. The industry can utilize this information to provide tenderness management strategies for each cut as well as improve the robustness of current tenderness predicting technology.
Keywords: beef; tenderness; trained panel